2020
DOI: 10.1111/den.13878
|View full text |Cite
|
Sign up to set email alerts
|

Status of single‐balloon enteroscopy‐assisted endoscopic retrograde cholangiopancreatography in patients with surgically altered anatomy: Systematic review and meta‐analysis on biliary interventions

Abstract: Background and Aims: Endoscopic retrograde cholangiopancreatography (ERCP) in patients with surgically altered anatomy is still challenging. Usefulness of single-balloon enteroscopy (SBE)-assisted ERCP has been increasingly reported. Short SBE is considered beneficial with a 152-cm working length and a 3.2-mm working channel. This has increased the variety of devices that can be used during ERCP procedures. The aim of this pooled analysis was to evaluate the efficacy of SBE-assisted ERCP in patients with surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 44 publications
(118 reference statements)
2
44
0
Order By: Relevance
“…Endoscopic retrograde cholangiopancreatography-related procedures have been reported to be successful in approximately 95% of cases [ 10 , 58 ]. However, it is sometimes difficult to complete the procedure in many situations, such as difficult biliary cannulation and surgically altered anatomy [ 59 , 60 ]. Moreover, distal malignant biliary obstruction could cause duodenal obstruction due to invasion; therefore, it is impossible to reach the papilla in such a situation.…”
Section: Endoscopic Ultrasound-guided Biliary Drainagementioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography-related procedures have been reported to be successful in approximately 95% of cases [ 10 , 58 ]. However, it is sometimes difficult to complete the procedure in many situations, such as difficult biliary cannulation and surgically altered anatomy [ 59 , 60 ]. Moreover, distal malignant biliary obstruction could cause duodenal obstruction due to invasion; therefore, it is impossible to reach the papilla in such a situation.…”
Section: Endoscopic Ultrasound-guided Biliary Drainagementioning
confidence: 99%
“…The latest systematic review and meta-analysis reported that the pooled data reaching the target site, biliary cannulation, and procedural success rates were 86.6%, 90%, and 75.8%. Adverse events occurred in 6.6% of the procedures [23]. Fatal pancreatitis and intestinal perforation requiring surgical operation were included in the report.…”
Section: Single Balloon-assisted Ercpmentioning
confidence: 99%
“…In these cases, device-assisted enteroscopes are usually necessary [25] . Access to the entero-enteric anastomosis is usually straightforward, avoiding the passage of the stomach and ligament of Treitz.…”
Section: Other Anatomy -Intact Papillamentioning
confidence: 99%